A9.3 Deletion of mPGES-1 affects Fatty Acid Composition and Eicosanoid Profiles in Mice. (25th February 2013) - Idborg, Helena; Olsson, Petter; Leclerc, Patrick; Raouf, Joan; Jakobsson, Per-Johan; Korotkova, Marina
Abstract : Background: mPGES-1 is considered an attractive alternative target for anti-inflammatory treatment with improved selectivity and safety compared to NSAIDs. Genetic deletion or pharmacological inhibition of mPGES-1 activity or expression down-regulate inflammation and pain in experimental models of arthritis. However, a detailed understanding of the molecular mechanisms and pathways affected by deletion/inhibition of mPGES-1 is essential before mPGES-1 inhibitors can safely be applied in the clinics. Objectives: To investigate the effect of mPGES-1 deletion on the levels of bioactive lipid mediators such as the eicosanoids (down-stream cascade) and fatty acids (up-stream cascade). Methods: Peritoneal macrophages (PM) from wild type (WT) and knock-out (mPGES-1 -/-, KO) mice were induced with LPS for 16 h. Cells were harvested for gene expression analysis and supernatants were collected for eicosanoid analysis. Gene expression profiling in WT and KO macrophages was performed using the microarray analysis (Applied Biosystems). Eicosanoid profiling of approximately 30 compounds was performed using LC-MS/MS. Fatty acid composition of total lipids in spleen and brain homogenates of WT and KO mice were determined using GC/FID. Results: Microarray analysis revealed that genetic deletion of mPGES-1 affected expression of genes related to lipid metabolism and mainly associated with eicosanoid, fatty acid and phospho- lipid metabolism, (e.g., Pla1A, Ptgis, Fabp3, Cept1, Comt etc). Compared to WT, mPGES-1 deficient PM displayed a markedly attenuated increase in PGE2 production upon LPS stimulation, and exhibited significantly increased levels of PGD2 metabolites such as 15-deoxy-∆ 12, 14 PGJ2 and 15-deoxy-∆ 12, 14 PGD2 (p < 0.05). There were significant differences in the fatty acid composition in spleen (e.g., palmitoleic acid decreased in KO, p < 0.05) and brain (e.g., myristic acid decreased in KO, p < 0.05) of KO and WT mice, suggesting that feed-back mechanisms are alternated by the deletion of m-PGES-1. Conclusions: Data reveals that mPGES-1 deficient PMs displayed shunting towards PGD2 pathway, i.e., towards anti-inflammatory metabolites, upon LPS stimulation compared to WT PMs. Moreover, mPGES-1 depletion alters the fatty acid composition of tissue lipids. These effects of inducible PGE2 on lipid metabolism have important implications for future mPGES-1 inhibitors and deserve further investigation.